An approach to prepare high-purity TiSi2 for clean utilization of Ti-bearing blast furnace slag. Issue 8 (7th April 2022) - Li, Zhanchao; Lei, Yun; Ma, Wenhui; Zhang, Yakun; Wang, Shiding; Ren, Yongsheng; Lv, Guoqiang
Abstract : An approach to achieve the dual purposes of the simultaneous preparation of high-purity TiSi2 and the clean utilization of Ti-bearing blast furnace slag. Abstract : The large amounts of accumulated titanium (Ti)-bearing blast furnace slag are not only an industrial waste but also an important Ti resource. TiSi2 is widely used in high-tech industries and is normally prepared using high-purity Ti and Si as the raw materials. In this study, a new approach, Si–Ti solvent refining, has been proposed to prepare high-purity TiSi2 using Ti-bearing blast furnace slag and low-purity Si as raw materials. First, TiO2 in Ti-bearing blast furnace slag was reduced by low-purity Si to form a raw Si–Ti alloy. Then, different amounts of low-purity Si were added to the raw Si–Ti alloys to obtain three different Si–Ti solvents (Si–39.6 wt% Ti, Si–35 wt% Ti, and Si–30 wt% Ti), which were used for the solvent refining of TiSi2 . The three Si–Ti solvents were then separated into TiSi2, eutectic Si–Ti alloy, and agglomerated impurities via electromagnetic directional crystallization to obtain pure TiSi2 crystals. The results showed that the removal ratios of impurities were significantly enhanced by Si–Ti solvent refining. When using the Si–30 wt%Ti% solvent, the largest removal ratios of Fe, Mn, Ni, Mg, Al, and Ca impurities in the region of agglomerated TiSi2 crystals were 76.5 ± 0.5%, 62 ± 0.5%, 80 ± 0.5%, 94.5 ± 0.5%, 86 ± 1%, and 93 ± 1%, respectively. The purity of the region containing agglomerated TiSi2 crystals was 99.32 ± 0.01%. Finally, the purification mechanism of TiSi2 crystals by Si–Ti solvent refining is discussed in terms of thermodynamics. This study provides a new technical route for the green, efficient, and economical utilization of Ti-bearing blast furnace slag. It also provides a new method for preparing high-purity TiSi2 alloy using low-purity raw materials.